(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Instruction 67/2011 SEDEF/MINISDEF/ESPAÑA regulates the procurement process of material resources accounting for their life cycle. In order to undertake an initial evaluation of the programmes that meet the conditions of the solution required, life cycle cost estimation is used as decision-making tool. The purpose of this paper is to present the procedure in place for estimating the life cycle costs (LCC) of programmes in Spain by comparing it to those of the major organisations to which we belong (NATO/ OCCAR), and verifying the use of historical and technical information, parameters and breakdown structures from September 2011 onwards in the LCC estimates performed.